Muscle Wasting after 48 Hours of Food Deprivation Differs between Mouse Strains and is Promoted by Myostatin Dysfunction - Petras Minderis; Indrė Libnickienė; Aivaras Ratkevičius (Lithuanian Sports University, 2018)
Background. Genetic factors play an important role in determining muscle mass. Indeed, myostatin dysfunction is associated with a pronounced muscle hypertrophy. The aim of our study was to test the hypothesis that starvation induced muscle wasting differs between BEH+/+ and C57BL/6J strains of mice and myostatin dysfunction prevents muscle wasting in BEH strain. Methods. 18-week-old males of C57BL/6J, BEH+/+ and BEH were subjected to 48 h food deprivation (FD). C57BL/6J mice were representatives of classic mouse strain. BEH mice which differ from BEH+/+ mice by Compact mutation in the Mstn gene represented a model for myostatin dysfunction.  All mice were divided into experimental and control groups. The control groups consisted of mice fed ad libitum. Seven mice were studied in each group. Mice were weighed before as well as 24 h and 48 h after FD which was followed by dissection and weighing of the hindlimb skeletal muscle. Results. BEH and BEH+/+ mice showed a similar (16.9 ± 1.4% vs. 19.3 ± 2.4%, p > .05) loss of body mass while loss of body mass in C57BL/6J mice was the greatest (24.8 ± 1.9%, p < .001) after FD. The loss of muscle mass was significant in both BEH (p < .001) and C57BL/6J (p < .01) mice, but it was below the level of significance (p > .05) in BEH+/+ mice. Conclusions. Myostatin dysfunction promotes muscle atrophy after FD. During short periods of FD, BEH+/+ mice are more resistant to body and muscle loss compared to C57BL/6J mice. Keywords:  myostatin deficiency, food withdrawal, starvation, muscle atrophy.